Analisis Perbandingan Kinerja Keuangan Bank Umum Syariah Hasil Spin-Off dan Hasil Akuisisi - Bagus Jaya Firdaus; Diharpi Herli Setyowati (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
This research is a study that compares the financial performance of Sharia Commercial Bank spin-off and acquisition. This research used BJB Syariah Bank and BNI Syariah Bank as a sample from Syariah Bank of spin-off result meanwhile Bank BRI Syariah, Bank BCA Syariah, and Bank Syariah Bukopin as sample from Sharia Public Bank of acquisition result. This research uses annual data for the period 2015-2017. Data analysis technique used is different test by using hypothesis test Independent Sample T-Test and the Mann Whitney U Test. The results of this study indicate that from the results of different tests there is no significant difference from the financial performance of the Islamic Commercial Banks resulting from spin-offs and the results of Acquisitions in financial ratios CAR, ROA, FDR, NPF, and BOPO.